2003
DOI: 10.1046/j.1365-2222.2003.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of allergic reaction by λ‐carrageenan: Toll‐like receptor 4/MyD88‐dependent and ‐independent modulation of immunity

Abstract: lambda-Carrageenan was suggested to be a useful dietary supplement to ameliorate allergic reactions while maintaining oral tolerance-dependent intestinal homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 40 publications
7
64
1
4
Order By: Relevance
“…Moreover, several studies have shown the effect of carrageenan induced inflammation on inflammatory marker release. Intrapleural administration of carrageenan into the pleural space prompts non-specific inflammatory reactions, which in turn stimulate the activation of innate immunity and peripheral release of TNF-a (Tsuji et al, 2003). In agreement with our results, de Oliveira et al…”
Section: Effect Of Inflammation On Inflammatory Markers Tumor Necrosisupporting
confidence: 93%
“…Moreover, several studies have shown the effect of carrageenan induced inflammation on inflammatory marker release. Intrapleural administration of carrageenan into the pleural space prompts non-specific inflammatory reactions, which in turn stimulate the activation of innate immunity and peripheral release of TNF-a (Tsuji et al, 2003). In agreement with our results, de Oliveira et al…”
Section: Effect Of Inflammation On Inflammatory Markers Tumor Necrosisupporting
confidence: 93%
“…The generation and expansion of T regulatory cells have been shown to depend on bacterial antigens and DNA (28,40). In line with these findings, several studies have highlighted the effects of bacterial components, through TLR2 and TLR4 signaling, on OT and the allergic response in animal models (2,44,46). Interestingly, in a recent study with humans (45), TLR-mediated inhibition of allergic inflammation by lipopolysaccharide was observed only in atopic children and not in adults.…”
Section: Discussionmentioning
confidence: 82%
“…TLR2 was found to be a receptor for peptidoglycan and lipoprotein by dimerizing with TLR6, whereas TLR4 was reported as a lipopolysaccharide and lipoteichoic acid receptor (19,32). Lipoteichoic acids are found in most grampositive bacteria (including lactobacilli), and the induction of oral tolerance to ovalbumin has recently been reported through the stimulation of Th1 cells via TLR4 signaling (33). Hence, L. paracasei could induce and maintain oral tolerance to BLG through the recognition of TLR4 by its lipoteichoic acids, but this hypothesis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%